3 Floor Luxury House Structure Design Planning Using ETABS Software - Fera Aysha; Meilandy Purwandito; Haikal Fajri (Portal: Jurnal Teknik Sipil, 2023)
Structural planning is a mixture of basics with science in structural analysis, statics, mechanics of materials and dynamics to obtain structures that are safe and economical in their service life. The purpose of this study was to plan the dimensions of the building's portal structure that can withstand loads safely. This research was conducted in Karang Asem 1, Kuningan, Setia Budi, South Jakarta. The final result of structural planning can be concluded that there are several beams used including, 450/600 beams, 450/700 beams, 500/700 beams, 550/700 beams, 600/750 beams, 450/650 beams, 400 beams /550, and ring beams. All of the above beams use D16 longitudinal reinforcement with d10 stirrup reinforcement. while the columns used are 400/350 columns, 400/400 columns, 450/450 columns and 450/500 columns using D16 longitudinal reinforcement with d10 stirrup reinforcement. And the 650/650 column uses D22 for longitudinal reinforcement and d10 for stirrup reinforcement.Keywords: Reinforced concrete structure, ETABS software, Planning, design, house, 3rd floor